Acute toxicity of natural and synthetic clothing fibers towards Daphnia magna: Influence of fiber type and morphology - Barrick, Andrew; Boardwine, Alison J; Nguyen, Nhung H A; Sevcu, Alena; Novotna, Jana; Hoang, Tham C (The Science of the total environment, 2025)
Environmental consequences of plastic pollution have come under scrutiny over the past 20 years as stewardship of the biosphere has risen in popularity. Microplastic research has focused on fragmented particles from hard plastics with limited research focused on microfibers released from textiles, which constitute a significant portion of microplastics in aquatic environments. The present study investigated hazards associated with two natural microfibers (cotton and silk) and four synthetic microfibers (acrylonitrile, Kevlar, nylon, and polyester) towards Daphnia magna. Results demonstrated that toxicity is dependent on the polymer type and morphology. Natural microfibers had no significant effects on D. magna whereas nylon microfibers were acutely toxic. While the total number of microfibers in exposure chambers contributed to microfiber ingestion and toxicity, suspended microfibers were weakly correlated to microfiber ingestion and toxicity. Microfibers with smoother surfaces were more toxic than microfibers that were frayed. Toxicity was more strongly related to microfiber ingestion than exposure concentration, suggesting that microfiber uptake is an important measurement endpoint for characterizing effects. Research with longer exposure times and emphasis on endpoints other than survival, such as uptake and retention of microfibers, feeding rates, growth and development, and reproduction are needed to understand the ecotoxicity of microfibers.
Keywords: Daphnia magna; Daphnia; Plastics; plastické hmoty; Microfiber exposure and uptake; textilie; zvířata; odívání; testy akutní toxicity; Textiles; Suspension stability of microfibers; Morphological effects of microfibers; Water Pollutants, Chemical; Natural vs synthetic fibers; Animals; Microfiber acute toxicity; Clothing; Toxicity Tests, Acute; chemické látky znečišťující vodu